Tracking moving object beyond the optical memory effect. (January 2020) - Lu, Dajiang; Liao, Meihua; He, Wenqi; Pedrini, Giancarlo; Osten, Wolfgang; Peng, Xiang
Highlights: Have presented a noninvasive single shot technology to recover the optical transfer function (OTF) of a scattering system. By utilizing the retrieved OTF and a simple and fast optimization method, the moving object can be tracked and imaged beyond the optical memory effect range. A composited OTF (CTOF) was introduced for extending the field of view (FOV). An extended object with size larger than OME range, can be reconstructed by just one single deconvolution operation with the COTF and there is no need any post-processing technique such as image mosaic. Abstract: The ability to track and image a moving object hidden behind scattering medium provides a crucial advantage when it is impossible or unpractical to physically invade the obstacles. Recently, a few methods based on optical memory effect (OME), especially speckle autocorrelation technology and deconvolution-based methods, have demonstrated that it is possible to reconstruct an object hidden from view. However, these methods do not allow for the noninvasive tracking and imaging a moving object in real time. We present a noninvasive single shot technology to recover the optical transfer function (OTF) of the scattering system. As the object moves, a simple and fast optimization of the OTF is employed to overcome the limitation of the tracking range as well as the restriction of the field of view (FOV), enabling sharp reconstructed images when object travels cross over the edge of OME. Experimental demonstration is presented to verify the feasibility of proposed method.